Microbiological Quality and Presumptive Enterobacter Contamination in Beef Liver Sold at Traditional Markets in Sidoarjo City - Agustin, Kurnia Dwi; Isnawati (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the microbiological quality of beef liver sold in traditional markets in Sidoarjo City by determining the total plate count (TPC) of total microorganisms and Enterobacteriaceae, as well as conducting presumptive identification of the genus Enterobacter through biochemical testing. The TPC results for total microorganisms showed that 7 of the 10 samples exceeded the maximum limit specified by the Indonesian National Standard (SNI). In addition, all 10 samples exceeded the Enterobacteriaceae limit established in SNI 9159:2023. Biochemical test results indicated that isolate B2, obtained from Porong Market, exhibited characteristics similar to those of Enterobacter cloacae, namely indole (–), H₂S (–), motility (+), methyl red (MR) (–), Voges–Proskauer (VP) (+), citrate (+), and urease (+). The high levels of microbial contamination indicate that beef liver samples from traditional markets in Sidoarjo City did not meet the microbiological standards for safe consumption. Therefore, to obtain its nutritional benefits while minimizing the risk of microbial infection, beef liver should not be consumed raw and should be cooked thoroughly at approximately 70°C.